ANALISIS PENGARUH TEKNOLOGI, FITUR DAN KEAMANAN DATA TERHADAP KEPUTUSAN MENGGUNAKAN APLIKASI “AJAIB” SEBAGAI TEMPAT INVESTASI - Aditya Rian Ramadhan; Perli Iswanto; Natallios Peter Sipasulta (Jurnal Ekonomi dan Manajemen, 2022)
This study aims to analyze the effect of technology, features, and data security on the decision to use the AJAIB application as an application for investment. The data collection method used in this study uses a descriptive method with a regression approach and Nagelkerke R Square is a method that aims to describe the magnitude of the influence and relationship of something that is ongoing at the time the research is conducted. The population in this study are people who use AJAIB applications who are domiciled in the DKI Jakarta area. The data analysis technique used by the author in this study is to use validity testing tools, reliability tests, Likert scales, binary logistic regression tests, and Nagelkerke R Square tests. The results in this study are, technology variables, features and data security have a positive and significant effect